Background Papers written for the Economic and Planning Council for Karnataka Volume III Issues in Planning - Planning Commission (Planning Commission, 1983)
There is a widespread consensus that the maintenance of Government’s assets is poor. There are several reasons for this, as this paper seeks to argue: for some assets, specific norms for maintenance have not been devised; for other assets, although specific norms may exist they are insufficiently sensitive to the variations in the maintenance requirements that may be needed for different locations or for different qualitative specifications of the assets; for yet other assets, maintenance may be poor simply on account of insufficient financial resources. With inadequate maintenance of assets over time, ensuring a respectable standard of administration becomes increasingly problematic, and the cumulative damage caused to assets can be undone only by upgrading the standards of maintenance.
Government of Karnataka